Patients with life-threatening arterial renal hemorrhage: CT angiography and catheter angiography with subsequent superselective embolization - Sommer, Christof-Matthias; Stampfl, Ulrike; Bellemann, Nadine; Ramsauer, S.; Lönard, Brigitta Michaela; Haferkamp, Axel; Hallscheidt, Peter; Richter, Götz Martin; Kauczor, Hans-Ulrich; Radeleff, Boris (CardioVascular and interventional radiology, 2010)
The purpose of this study was to evaluate the technical and clinical success of superselective embolization in patients with life-threatening arterial renal hemorrhage undergoing preinterventional CT angiography. Forty-three patients with clinical signs of life-threatening arterial renal hemorrhage underwent CT angiography and catheter angiography. Superselective embolization was indicated in the case of a positive catheter angiography. Primary study goals were technical and clinical success of superselective embolization. Secondary study goals were CT angiographic and catheter angiographic image findings and clinical follow-up. The mean time interval between CT angiography and catheter angiography was 8.3 ± 10.3 h (range, 0.2-34.1 h). Arterial renal hemorrhage was identified with CT angiography in 42 of 43 patients (98%) and catheter angiography in 39 of 43 patients (91%) (overview angiography in 4 of 43 patients [9%], selective angiography in 16 of 43 patients [37%], and superselective angiography in 39 of 43 patients [91%]). Superselective embolization was performed in 39 of 43 patients (91%) and technically successful in 37 of 39 patients (95%). Therefore, coil embolization was performed in 13 of 37 patients (35%), liquid embolization in 9 of 37 patients (24%), particulate embolization in 1 of 37 patients (3%), and a combination in 14 of 37 patients (38%). Clinical failure occurred in 8 of 39 patients (21%) and procedure-related complications in 2 of 39 patients (5%). The 30-day mortality rate was 3%. Hemoglobin decreased significantly prior to intervention (P < 0.001) and increased significantly after intervention (P < 0.005). In conclusion, superselective embolization is effective, reliable, and safe in patients with life-threatening arterial renal hemorrhage. In contrast to overview and selective angiography, only superselective angiography allows reliable detection of arterial renal hemorrhage. Preinterventional CT angiography is excellent for detection and localization of arterial renal hemorrhage and appropriate for guidance of the embolization procedure.
Gesehen am 16.08.2023